Proposta de regulamentação do enquadramento dos corpos de água do estado de Mato Grosso : subsídios à gestão dos recursos hídricos - Noquelli, Luiz Henrique Magalhães (2016)
The State Water Resources Policy is set by Law No. 6945 of 1997 and is in strict accordance with the National Policy, striving for integrated, decentralized and participatory management where the management tools: the State Water Resources Plan; Classes in the framework of Water Bodies; the Law Granting use of water resources; the Information System on Water Resources; and Charging for the use of water resources and the system structure formed by the State Water Resources Council (CEHIDRO), the Agency Coordinator / Manager the Secretary of State for the Environment (SEMA) and the Basin Committees (CBH), with same logic, keeping the allocation of spheres. The framework is the establishment of quality level (class) to be achieved and / or maintained in a segment of the water body over time, which allows the integration of environmental policy and water resources, guiding the state's development actions. This work was conducted using the main national laws as the theme "environment", as follows: Law No. 9.433 / 97 establishing the National Water Resources Policy, CONAMA 357/2005, resolution which provides for the classification of water bodies and environmental guidelines for its framework and establishes the conditions and effluent discharge standards, CONAMA 396/2008 resolution which provides for the classification and environmental guidelines for the classification of groundwater and CNRH 91/2008, Resolution providing for General procedures for the classification of surface and underground water bodies. As for the States, how to develop the work it was also a survey of the laws with the focus on the environment, and the 10 states chosen: Alagoas, Bahia, Mato Grosso do Sul, Minas Gerais, Santa Catarina, Paraíba, Paraná, Rio Grande do Norte, Rio Grande do Sul and São Paulo. This choice was due to the publication by the National Water Agency - ANA's book Situation of Water Resources in 2009 Brazil, which mentioned that these were the first Brazilian states to work with the framework. The Instrument framework will enable the State can realize the water management to prevent future conflicts, breaking the paradigm of only act when the problem is already real. As a product will be submitted two (2) bills a Government Decree regulating the management tool and a resolution of the State Water Resources Council, defining the procedures to be followed for the execution in the state. The course will be through the Superintendency of Water Resources, which holds the organ function Coordinator / Manager and Executive Secretary of CEHIDRO. Approval and publication will assist the environmental authority for decision-making, allowing preventive measures to combat pollution.